THE EFFECT OF DIFFERENT DOSAGE OF TUBIFEX SP ON THE GROWTH AND SURVIVAL RATE OF BLACK GHOST FISH (Apteronotusalbifrons) - Yosha Arianti; Rusliadi Rusliadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aims to determine the effect of giving Tubifexsp with different doses on the growth and survival of black ghost fish (Apteronotusalbifrons). This research was conducted in May – July 2019 at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Affairs, Riau University, Pekanbaru. This study used a one-factor Completely Randomized Design (CRD) consisting of four treatment levels with three replications so that 12 experimental units were needed. The treatments were: Giving Tubifexsp 5%, 10%, 15% and 20% of the weight of fish biomass. The results of the research that have been carried out can be seen that the best treatment is feeding with a dose of 20% / body weight which can produce an absolute weight growth rate (0.51 g), absolute length growth (4.75 cm), specific length growth (2, 5 cm). 20%) and survival (86.67%) while the water quality parameters during the study obtained pH 6.0-7.0, temperature 26-28 0C, DO 3.1-3.2 mg/l.Keyword :Apteronotusalbifrons, Doses, Growth of Tubifexsp